The Effect of IT Use on Organizational Performance in Terms of Organizational Learning in the Healthcare Industry - Andri Rianawati; Faizal Susilo Hadi; Ahmad Johan (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2022)
The use of IT has been massively used in improving organizational performance, including the performance of health institutions. Improved performance can be achieved by various schemes, one of which is increasing organizational learning. For this reason, this study is an attempt to examine information and technology in an effort to increase absorptive capacity in the role of organizational learning in the health care industry. The method used in this research is quantitative with an online survey. Structural equation modeling is used to analyze the path analysis test. The results of this study indicate that IT has a positive influence on organizational learning, both the first outcome, namely knowledge transfer and the second outcome, namely absorptive capacity, as well as on the performance of health care institutions. This research provides both theoretical and practical contributions. The theoretical contribution is adding literacy related to IT functions to improve organizational performance in the role of organizational learning. While, the practical contribution is to provide a view that in the implementation of IT it is necessary to pay attention to organizational learning so that IT functions properly.